Assessing the impact of tech-driven solutions to manage COVID-19 in Saudi Arabia: insights from health information technology professionals - Farhah, Nesren S. (Frontiers in Public Health, 2024)
IntroductionThe outbreak of the COVID-19 pandemic has disrupted the provision of healthcare services, forcing health systems, governments, and other public health stakeholders to embark on alternative means to deliver care.MethodThis scenario has fueled the adoption of digital health technologies in the healthcare industry to enhance the management of the COVID-19 pandemic. This study aimed to investigate the effect of using health information technologies (HITs) in managing the COVID-19 pandemic in Saudi Arabia from the health information technology professionals' perspectives. In addition, the study aimed to evaluate the usefulness of using HITs interventions to manage COVID-19, assess HITs information exchange capability and quality, and measure practitioners' satisfaction with HITs.ResultsThe present study used a primary analysis and cross-sectional design. Data were collected using survey questionnaires and analyzed. A total of 371 participants (n = 371) responded to the questionnaire that was administered online, in March 2022. The study found that HITs significantly influenced the management of the COVID-19 pandemic in various areas, including consulting, screening, and monitoring. However, technical issues, among other challenges, hindered the realization of the desired outcomes.DiscussionIn addition, the study found HITs helpful in managing COVID-19, adding that these technologies improved providers' satisfaction concerning access to and value of information. The study found the need to address the challenges associated with HITs that prevent the effective deployment of HITs to manage COVID-19 and future pandemics.